Vers une réforme des pouvoirs de la police en Angleterre - Leigh, Leonard (Les Cahiers de droit, 1979)
The author discusses certain reforms to the law of police powers which are currently being demanded by the English police. He notes that the English police have long acted under a regime of limited powers. These have proven to be irksome, but they have also conduced to a regime under which the police use the minimum powers possible and rely considerably on public support in the fight against crime. The police however urge that further powers are necessary, notably powers to stop and question persons in public places and to hold arrested persons for interrogation concerning the commission of offences before charging the person or bringing him before a magistrate. These wide powers resemble those of certain other systems, notably France, the practical workings of which are comparatively little known in Britain. They are of doubtful legality in view of the European Convention on Human Rights. The author questions the necessity for and the desirability of such powers. He contends that they are apt to be abused, and that the French experience affords a guide to what might happen. He argues that formal powers are no substitute for public support. He fears that powers to stop and search will cause resentment, and that little countervailing practical benefit will result from them. As regards powers to detain persons before charging, he argues that such procedures will erode existing civil liberties safeguards and that certain proposed safeguards such as limiting the time available to the police for detention will prove ineffectual. There will be little time to inform defence lawyers of the nature of the case at an early stage and magistrates will probably support the police. If detention is to be allowed judicial permission should, as a general rule, be sought in advance from a High Court Judge. Here he advances a model based upon the experience of Cyprus. The author also considers, briefly, the modalities of interrogation. He considers that the suspect must continue to have a right to silence. He must also have the right to the timely assistance of a defence lawyer, a right which presently is too often subverted by the practice. The author considers also that thought should be given to the question whether a suspect should have the right to the assistance of a lawyer during police interrogation. The author concludes that in assessing the nature of and necessity for accretions and additions to police powers, the English should not lose sight of their historic attachment to civil liberties.